Modern methods of seawater desalination - Levadnii, O. O. (ТДАТУ, 2021)
The shortage of fresh water is a real threat for the entire planet. The world knows such ways of solving the problem as transporting icebergs, transferring runoff from high-water rivers, and desalination, but they are not used in all parts of the planet. There is a sufficient amount of enough sea water, mineralized and waste waters and desalination would make it possible to forget about fresh water shortages forever.
Keywords: water resources; desalination